The Effect of Vernalization on the Appearance of Local Amaryllis (Hippeastrum sp.) Plants in the Land of Karo and West Sumatera - Ulfa Ridha Andini; Hot Setiado; Luthfi Aziz Mahmud Siregar (Talenta Publisher, 2019)
Amarilis is one of the flower of the park that is attractive and has high economic value. This study aims to determine the effect of vernalization on the appearance of local amaryllis plants in Tanah Karo and West Sumatra. This research was conducted at the Plant Breeding Basic Laboratory of the Faculty of Agriculture, University of North Sumatra, Medan, from February 2018 to July 2018. This research was carried out by storing tubers at room temperature (control) and storage of tubers at low temperatures (vernalization) at 10 oC for 6 weeks, and with differences in accession of plants namely G1 (Accession of West Sumatra Payakumbuh), G2 (Bukit Tinggi West Sumatra Accession), G3 (Padang Panjang West Sumatra Accession), G4 (Local Kabanjahe Accession Tanah Karo), G5 (Berastagi Local Accession Tanah Karo ), G6 (Tanah Karo Local Accession Accession). The results showed that vernalization gave a different appearance compared to the control treatment.